Real-World Experience of Telbivudine and Lamivudine as Antiviral Prophylaxis for Chemotherapy-Related Hepatitis B Reactivation - Lianda Siregar; Imelda Maria Loho; Agus Sudiro Waspodo; Siti Nadliroh; Rahmanandhika Swadari; Rizka Andalusia; Leovinna Widjaja (Indonesian Journal of Cancer, 2021)
Background: There is currently no data regarding the efficacy of prophylactic telbivudine in hepatitis B patients undergoing chemotherapy. This study aims to describe the results of preemptive telbivudine and lamivudine to prevent chemotherapy-related HBV reactivation.Methods: The medical records of all patients with HBsAg positive or HBs-Ag negative, anti-HBc positive, who were referred to the hepatology clinic between May 2014 and December 2016, were retrospectively reviewed. As this is a descriptive study, no statistical analysis was done.Results: A total of 52 patients with prophylactic telbivudine or lamivudine therapy were included, with 26 patients in each group. Rituximab-based treatment was given in nine and five patients in the telbivudine and lamivudine group, respectively. The number of patients who completed antiviral treatment up to six months after chemotherapy was 17 patients in each group. There was less incidence of HBV reactivation in the telbivudine group (2 of 17 patients, 11.8%) than in the lamivudine group (7 of 17 patients, 41.2%). Delayed reactivation was noticed in 1 of 2 patients in the telbivudine group and 3 of 7 patients in the lamivudine group. The median log10[HBV DNA] at reactivation was 4.52 (1.70 – 8.35) IU/mL. Severe hepatitis was observed in two patients in the lamivudine group and one patient in the telbivudine group. Of 34 patients who completed antiviral treatment, two patients died due to primary cancer. No interruption of chemotherapy or mortality due to hepatitis was noticed in both groups.Conclusions: Preemptive telbivudine or lamivudine in HBsAg positive or HBsAg negative, anti-HBc positive patients seems to be a good treatment option.